Quantifying the effects of learning styles on attention - Durães, Dalila (2017)
Monitoring and managing attention in the classroom is nowadays an important aspect where the level of learner’s attention affects learning results. When students are using devices connected to the Internet in learning activities in which they send and received notifications, beeps, and vibrations and blinking messages, the ability to focus becomes increasingly important. This is true in many different domains, from the classroom to the workplace. This paper deals with the issue of attention monitoring, with the aim of providing a non-intrusive, reliable and easy tool that can be used freely in schools or organizations, without changing or interfering with the established working routines. Specifically, we look at desk students in learning activities, in which the student spends long time interacting with the computer.